2021
DOI: 10.1186/s12911-021-01397-x
|View full text |Cite
|
Sign up to set email alerts
|

Are health websites credible enough for elderly self-education in the most prevalent elderly diseases?

Abstract: Background The Elderly and their caregivers need credible health information to manage elderly chronic diseases and help them to be involved in health decision making. In this regard, health websites are considered as a potential source of information for elderlies as well as their caregivers. Nevertheless, the credibility of these websites has not been identified yet. Thus, this study aimed to evaluate the credibility of the health websites on the most prevalent chronic diseases of the elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…In this study, 1118 web pages of 48 Iranian universities of medical sciences related to health departments, faculties and hospitals of Iranian universities of medical sciences. They belonged to type 1 universities [ 19 ], type two universities [ 21 ], and type three universities [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 1118 web pages of 48 Iranian universities of medical sciences related to health departments, faculties and hospitals of Iranian universities of medical sciences. They belonged to type 1 universities [ 19 ], type two universities [ 21 ], and type three universities [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Gill et al (2013), showed that social media technologies and websites have the potential to deliver safe and effective health education[ 20 ]. In a study by Valizadeh-Haghi et al (2021), showed that websites can be used for health education to prevent diseases, but their scientific content needs to be verified and validated[ 21 ]. The Ministry of Health must use all the information facilities, such as the website of the universities of medical sciences, to inform and publish the correct news about coronavirus among people.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, patients from the delayed diagnosis group significantly more often than their timely diagnosis counterparts mentioned the Internet as a primary source of information about testicular cancer. This finding points to a growing problem of seeking medical information from unverified Internet resources instead of referring to a specialist [ 9 , 10 , 11 , 12 , 13 ]. This seems to be particularly widespread in the case of medical problems related to sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies demonstrated that the knowledge of the early symptoms of testicular cancer among males at risk is suboptimal [ 9 , 10 , 11 , 12 , 13 ], with the practice of testicular self-examination, a basic screening test, not being as common as recommended [ 14 , 15 , 16 , 17 , 18 , 19 ]. However, still little is known about the causes of diagnostic delay in men with testicular malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…However, health knowledge websites do not meet the needs of non-professionals. First, there are too many websites and some of them are not credible enough [ 29 ]. For nonprofessionals, it is also difficult to spot problems in time.…”
Section: Introductionmentioning
confidence: 99%